Mitochondria-Targeted Biomaterials-Regulating Macrophage Polarization Opens New Perspectives for Disease Treatment - Tian Z; Wang X; Chen S; Guo Z; Di J; Xiang C (International Journal of Nanomedicine)
Zui Tian,* Xudong Wang,* Shuai Chen,* Zijian Guo, Jingkai Di, Chuan Xiang Department of Orthopedics, Second Hospital of Shanxi Medical University, Taiyuan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chuan Xiang, Department of Orthopedics, Second Hospital of Shanxi Medical University, Taiyuan, People’s Republic of China, Email chuanxiang@sxmu.edu.cnAbstract: Macrophage immunotherapy is an emerging therapeutic approach designed for modulating the immune response to alleviate disease symptoms. The balance between pro-inflammatory and anti-inflammatory macrophages plays a pivotal role in the progression of inflammatory diseases. Mitochondria, often referred to as the “power plants” of the cell, are essential organelles responsible for critical functions such as energy metabolism, material synthesis, and signal transduction. The functional state of mitochondria is closely linked to macrophage polarization, prompting interest in therapeutic strategies that target mitochondria to regulate this process. To this end, biomaterials with excellent targeting capabilities and effective therapeutic properties have been developed to influence mitochondrial function and regulate macrophage polarization. However, a comprehensive summary of biomaterial-driven modulation of mitochondrial function to control macrophage phenotypes is still lacking. This review highlights the critical role of mitochondrial function in macrophage polarization and discusses therapeutic strategies mediated by biomaterials, including mitochondria-targeted biomaterials. Finally, the prospects and challenges of the use of these biomaterials in disease modulation have been explored, emphasizing their potential to be translated to the clinic. It is anticipated that this review will serve as a valuable resource for materials scientists and clinicians in the development of next-generation mitochondria-targeted biomaterials.Keywords: macrophages, polarization, biomaterials, mitochondria